The Influence of Job Satisfaction, Organizational Commitment on Employee Turnover and Performance at PT. Surya Tangerang Branch - Hadiwijaya, Dudung; Murniadi, Murniadi; Ardiyanti, Anita (The International Journal of Education Management and Sociology, 2024)
This research aims to test the influence between variables so that a level of accuracy can be achieved for PT employees. Surya Tangerang Branch. As non-permanent employees, the number of non-permanent employees in 2023 will be 62% of the total number of permanent employees. The turnover rate for non-permanent employees will reach 10.9% or as many as 37 employees in 2023. Factors that influence employee turnover. The research method uses SEM (Structural Equation Modeling) which is a multivariate analysis technique with 4 research variables, namely Job Satisfaction, Organizational Commitment, Employee Turnover, and Employee Performance. From these variables, five hypothesis formulations are used. This data was obtained from primary data directly from respondents through questionnaires distributed to non-permanent employees at the PT company. Surya Tangerang Branch. The number of respondents was 150 people, data analysis using SEM-PLS. The results of organizational commitment and job satisfaction have a significant influence on employee turnover, while the employee turnover and organizational commitment variables have a significant influence on employee performance, while the job satisfaction variable does not have a significant influence on employee performance. Suggestions for companies to continue providing training and skills regularly. For researchers to be able to add several variables to their research.